2015
DOI: 10.1016/j.neuroscience.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Association between exploratory activity and social individuality in genetically identical mice living in the same enriched environment

Abstract: Abstract-We previously reported that inbred, genetically identical mice living in one enriched environment develop individual behavioral trajectories, indicating increasingly different levels of spatial exploratory behavior as quantified by roaming entropy. Cumulative roaming entropy (cRE) correlated positively with adult hippocampal neurogenesis, a type of plasticity involved in the flexible integration of new information into existing contexts (Freund et al., 2013). The study on which we report here was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 30 publications
(51 reference statements)
2
59
2
Order By: Relevance
“…Additionally, many behavioral assays utilize the hindpaw in order to assess phenotypes such as pain, motor function, weight-bearing, locomotion, and exploratory behaviors (Gregory et al 2013; Pratt et al 2013; Pertici et al 2014; Freund et al 2015). For these reasons, a sustained peripheral drug delivery system is required in order to accurately study the physiology and behavior of neurological diseases in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many behavioral assays utilize the hindpaw in order to assess phenotypes such as pain, motor function, weight-bearing, locomotion, and exploratory behaviors (Gregory et al 2013; Pratt et al 2013; Pertici et al 2014; Freund et al 2015). For these reasons, a sustained peripheral drug delivery system is required in order to accurately study the physiology and behavior of neurological diseases in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that behavioral individualization in ENR can be detected using roaming entropy (RE) as a measure of territorial coverage and spatial exploration of the environment by individual mice 9,10 . Using the longitudinal mouse activity data obtained from the RFID recordings in the ENR cage, we calculated REs for the 40 mice of the ENR group and analyzed the development and stability of individual behavior during the six months of ENR housing.…”
Section: Enr Mice Develop Stable Individualized Trajectories In Explomentioning
confidence: 99%
“…We have previously shown that environmental enrichment (ENR) promotes the development of behavioral variability between inbred C57BL6/JRj mice and proposed that ENR could be used as a tool to study brain individualization [9][10][11] . In those experiments, inter-individual differences among inbred mice emerged when they were housed in the same ENR cage, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, RFID tags have been used to reliably identify individuals in combination with video data (Weissbrod et al, 2013). Additionally, while RFID alone does not provide sufficient spatial resolution to identify social behaviors, it does provide a method to collect long-term information (with much lower storage costs than video) about animal position (Freund et al, 2013(Freund et al, , 2015Perony et al, 2012). However, the smallest RFID tags currently available, 1 mm×8 mm and 30 mg, are still very large relative to insect model systems.…”
Section: Marking Individualsmentioning
confidence: 99%